Effectiveness of Sansavieria trifasciata Extract Bracelet in Absorbing Carbon Monoxide (Co) in Cigarette Smoke - gendis siti rahmawati; Resti Nuraeni; Lu’lu Robiatul Fajrin; Sistiana Windyariani (Biota, 2019)
Carbon monoxide (CO) contained in cigarette smoke is a very strong poison, if it is smoked by the lungs it will be easier to bind hemoglobin, so that red blood cells will lack oxygen, which can cause damage to blood vessels. with the process of atherosclerosis (narrowing). Sansevieria trifasciata has the ability to absorb poisons such as CO. This study aims to determine the effectiveness of Sansevieria trifasciata leaf extract in absorbing CO contained in cigarette smoke and assessing the amount of CO absorbed by Sansevieria trifasciata leaf extract. The method used is a pure experimental method using a Completely Randomized Design (CRD) consisting of 3 different treatments and 3 repetitions. The results of the 3 treatments showed that P1 (Sanseviera trifasciata wet extract) had the ability to absorb CO an average of 12.67 ppm every 15 minutes, in contrast to P2 (ethanol extract of Sanseviera trifasciata) which absorbs CO. 91.11 ppm every 15 minutes P3 (ethanol extract and CMC leaves from Sansevieria trifasciata) has the ability to absorb CO by 37.89 ppm every 15 minutes. The highest absorption effectiveness was obtained by ethanol extract and bracelets containing ethanol extract with the addition of CMC.